Extremal properties of a new generalized class of tilted analytic univalent functions / Nurin Hannani Halim ... [et al.] - Halim, Nurin Hannani; Shaffei, Nurul Natasya; Mahari, Intan Nur Syauqina; Yahya, Abdullah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Geometric function theory is a branch of complex analysis that aims to study the geometric properties of certain class of univalent functions. Other areas of mathematics, such as potential theory, hyperbolic geometry, and dynamical systems, have strong ties to the subject. Since a proper approach available in this project, determining the geometric properties is not an easy task since it involves many definitions and theorem. There are many classes of functions that can be explore. However, there are only a few methods that can be used to solve this problem. Method used to determine geometric properties of this function is using Herglotz Representative Theorem.